Improving the quality of teachers’ professional communication in distance learning at higher education institutions, using information and communication technologies - Synelnyk, I.; Stonoha, A. (Problems of Engineer-Pedagogical Education, 2021)
The topicality of the research topic is predefined by an urgent requirement put into place by the coronavirus pandemic and the need for quarantine measures. The effect of the virus has been seen in the transition of the existing in-class educational process into online studies. This major shift in education has stimulated the improvement of the system of online studies and communication by means of computer technology. The aim of this work is to expose problems in educational communication under the conditions of distance learning, to substantiate the choice and the use of information and communication technologies (ICT) in the solution of educational problems. To select a specific topic for research it is necessary to understand the features of professional communication in distance learning, to ground the problems of educational communication, to offer the ways of communication and decision-making, and to offer means suitable to solve problems in educational communication. While conducting the research, such methods as pedagogical supervision and questioning (questionnaires) were used. Features of teacher-student communication in distance learning, which had the strongest impact on the character of distance learning, were identified. Also, the advantages and limitations of work in such a mode were examined from the point of view of its participants. An empirical study was undertaken in the form of an electronic questionnaire administered to educators and students of higher education establishments of different types. Based on the results of the empirical research, the main advantages and problems of distance learning were distinguished, as were factors that promote or reduce the perception of quality and mastering of educational materials from the viewpoint of research and teaching staff and students. According to the results of the poll, the basic positive qualities of distance learning are the advantages of organizational character as well as the use and necessity of capturing modern ІCТ. Basic limitations and factors that negatively influence perception and learning in distance education are related to complex organization of teaching activities and educational cooperation and a decline in the perception of quality and mastering of educational materials. The results demonstrated that most problems of the educational process are conditioned by incomplete educational communication in the online mode. The solution of these problems is possible to carry out through information and communications technologies and the opportunities they offer.